Phoneme "Smallest pair" Phoneme "Language game" tool - Aulia, Winda; Yani , Rahma; Lubis , Yani (Jurnal Pendidikan Rafflesia, 2023)
The "bottom pair" phonemic data can be used as a "language game" tool because "Language Game" is: A language speaking company "Playing" with language, especially words, for a specific purpose/interest. Based on existing references, the phonemic problem "smallest pair" is used as a tool “Language games” has never been used as an independent research topic and is therefore of interest Education Information is obtained by listening and using different/contrasting methods using the comb/bait technique. Data type is lower than data common in many phonological definitions of speech Indonesia. Data analysis supports the application of language theory in the field of phonology, phonemic subfield. Recent research has identified five different "language game models". that is:1) templates: single vowel phoneme vs. monovocal phonemes, 2) patterned: two-vowel phoneme vs. Two vowel phonemes, 3) clause: vowel phonemes versus diphthong phonemes, 4) clauses: One Consonant phoneme versus consonant phoneme and 5) examples: two consonant phonemes versus two.